"Teach Your Daughters to Wail and One Another to Lament": Jewish Prayers and Liturgical Texts for Female Victims of Sexual Assault - Ben-Lulu, Elazar (Open theology, 2021)
Throughout generations, various prayers have been composed to express religious and cultural experiences of the Jewish community, such as holidays life-cycle and national tragedies. However, some social issues, such as sexual assault, have been excluded from this canon. This article uncovers Jewish prayers and liturgical texts dedicated to female victims of sexual assault. Drawing on a qualitative inquiry based on content analysis and interviews with the prayers’ authors, I demonstrate how these texts (re)position sexual assault victims in Jewish liturgy by including new phrasings and references to God; by removing masculine violence related to God; by mentioning biblical female characters who experienced sexual harassment; by denouncing of patriarchal abuse; or by sanctifying the woman’s painful body, which is incorporated as an important agent in the ritual’s structure. Therefore, I suggest considering these texts a political mean to voice women’s traumas and to incorporate them into the religious sphere, thereby rectifying a long-silenced discourse.